G553 Prevalence and pattern of prenatal alcohol exposure determined by alcohol biomarkers in newborn blood spot screening cards. (25th October 2020) - Henderson, EMA; Mactier, H; Favretto, D; Young, D
Abstract : Fetal alcohol spectrum disorder (FASD) is the commonest preventable cause of preventable neurodisability but is under-diagnosed. Earlier diagnosis helps prevent secondary effects of FASD, resulting in better educational attainment and earlier healthcare interventions. Maternal self-report of prenatal alcohol exposure (PAE) is negligible, despite 1 in 7 women in Scotland drinking alcohol in pregnancy, as determined by alcohol biomarkers in meconium (Abernethy et al). Phosphatidylethanol (PEth), a direct metabolite of ethanol can be measured from newborn dried blood spot cards. In adults, PEth is 100% specific for alcohol exposure in blood samples for up to 12 days after a single drink. Blood spots cards are collected from almost all infants in the UK on day five and stored; retrospective testing might be possible when FASD is suspected. Objective: To investigate the potential utility of newborn blood spot cards for the detection of PAE to determine prevalence. Population: Total population of infants delivering in a single maternity hospital on each fourth day (random sample). Methods: 840 mother and infant dyads were recruited over an 11-month period to provide meconium and blood spot samples. The latter were collected coincident with routine newborn screening, when the original heel prick bleeding allowed. Maternal and infant demographics were collected via a health questionnaire. Samples were frozen and analysed at the University of Padova. The study had REC approval; all mothers gave written informed consent. Results: Blood spot cards were collected from 510 infants; 502 (98.5%) were analysable for PEth. 216 (43.0%) samples were positive for PEth and in 148 (29.5%) the concentration was > 20 ng/ml, indicative in adults of significant alcohol exposure. In the recruited cohort, 13.8% of mothers admitted to alcohol consumption beyond 20 weeks of pregnancy, 14.5% of meconium samples were positive for ethylglucuronide and 39.6% positive for fatty acid esters. Conclusions: Analysis of newborn blood screening cards for PEth is feasible. There is a need for further data correlating PEth values in the newborn with other biomarkers. Cut off values used for adults may overestimate PAE.